Creation of a Leadership Plan 2023-2024 for the Board of Directors of the Charcot Group in the Canton of Tilarán - León, Litzy (2025)
The Charcot Group, located in Tilarán, Guanacaste, Costa Rica, provides care for older adults with neuropathies through activities that promote active aging, in collaboration with the University of Costa Rica (UCR) and the Universidad Estatal a Distancia (UNED). The objectives include evaluating UCR's work in 2022, developing a strategic vision, and enhancing the leadership skills of the Board of Directors. The methodology used is Action Research, which combines virtual interviews, in-person working sessions, and workshops to create an Action Plan for 2023-2024. The results highlight a plan that promotes the group's autonomy and improves leadership, ensuring better organization and functioning. This not only enhances the individual well-being of older adults but also contributes to overall social strengthening by preventing isolation and fostering interaction with other age groups.